Bodas de sangre de Federico García Lorca en las tablas húngaras. Algunas representaciones memorables entre 1957-2014 - Katona, Eszter (Acta Hispanica, 2014)
The House of Bernarda Alba was the first play of Federico Garcia Lorca that was staged by a Hungarian company in 1955. Hungarian directors followed with close attention the dramas of the Andalusian playwright and two years later, in 1957, the Hungarian National Theater included on its program another play of Lorca, Blood Wedding, written in 1933. Since then, the popularity of this drama on Hungarian stages has not diminished at all, it also inspired dance and opera adaptations. Recently, in the 2013-2014 season, Magyar Színház theater has also staged this play. The aim of this paper, which has been inspired by the aforementioned premiere, is to offer an overview of the Hungarian reception of Blood Wedding, highlighting some important productions of the past six decades.